Exploring the Influencing Factors of Innovative Incentive Mechanisms for Employees in Small and Medium-Sized Technology Enterprises - Wang, Xinshuo (Transactions on Economics, Business and Management Research, 2024)
With the development of the economy and the increasing demand for technology, technology-based enterprises have gradually become the main force driving world progress. The small and medium-sized technology enterprises play a crucial role and have an irreplaceable role in the economy. Employee motivation is an essential part of human resource management, which may boost productivity, rise the caliber of output, and encourage businesses to develop rapidly. However, due to the rapid development of these companies, there have been many issues with employee motivation. This article analyzes the problems of employee motivation in these enterprises and explores future development directions. Through research, it has been found that small and medium-sized technology enterprises still have shortcomings in employee motivation. This sort of enterprises should pay attention to the diversification of talent cultivation and incentive methods, as well as the demand for talent in the future, and take more actions to motivate employees.